BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

A preliminary assessment of CO2 capture, transport, and storage network for China's steel sector - Yuancheng Lin; Tubagus Aryandi Gunawan; Cecelia Isaac; Hongxi Luo; Fangwei Cheng; Eric D. Larson; Chris Greig; Linwei Ma; Zheng Li (Journal of Cleaner Production, 2024)

Agricultural conservation may not help Midwestern US freshwater biodiversity in a changing climate - Qihong Dai; Yong Cao; Maria L. Chu; Eric R. Larson; Cory D. Suski (Science of The Total Environment, 2023)

Association of cerebral microvascular dysfunction and white matter injury in Alzheimer’s disease - Zsolt Bagi; Christopher D. Kroenke; Katie Anne Fopiano; Yanna Tian; Jessica A. Filosa; Larry S. Sherman; Eric B. Larson; C. Dirk Keene; Kiera Degener O’Brien; Philip A. Adeniyi; Stephen A. Back (GeroScience, 2022)

Functional localization of audiovisual speech using near infrared spectroscopy - Iliza M. Butera; Eric D. Larson; Andrea J. DeFreese; Adrian KC Lee; René H. Gifford; Mark T. Wallace (Brain Topography, 2022)
Visual cues are especially vital for hearing impaired individuals such as cochlear implant (CI) users to understand speech in noise. Functional Near Infrared Spectroscopy (fNIRS) is a light-based imaging technology that is ideally suited for measuring the brain activity of CI users due to its compatibility with both the ferromagnetic and electrical components of these implants. In a preliminary step toward better elucidating the behavioral and neural correlates of audiovisual (AV) speech integration in CI users, we designed a speech-in-noise task and measured the extent to which 24 normal hearing individuals could integrate the audio of spoken monosyllabic words with the corresponding visual signals of a female speaker. In our behavioral task, we found that audiovisual pairings provided average improvements of 103% and 197% over auditory-alone listening conditions in −6 and −9 dB signal-to-noise ratios consisting of multi-talker background noise. In an fNIRS task using similar stimuli, we measured activity during auditory-only listening, visual-only lipreading, and AV listening conditions. We identified cortical activity in all three conditions over regions of middle and superior temporal cortex typically associated with speech processing and audiovisual integration. In addition, three channels active during the lipreading condition showed uncorrected correlations associated with behavioral measures of audiovisual gain as well as with the McGurk effect. Further work focusing primarily on the regions of interest identified in this study could test how AV speech integration may differ for CI users who rely on this mechanism for daily communication.

The FamilyTalk randomized controlled trial: patient-reported outcomes in clinical genetic sequencing for colorectal cancer - Sukh Makhnoon; Deborah J. Bowen; Brian H. Shirts; Stephanie M. Fullerton; Eric B. Larson; James D. Ralston; Kathleen A. Leppig; David R. Crosslin; David Veenstra; Gail P. Jarvik (Cancer Causes & Control, 2021)

Do roads or streams explain plant invasions in forested protected areas? - Melissa K. Daniels; Gwenllian D. Iacona; Paul R. Armsworth; Eric R. Larson (Biological Invasions, 2019)

Comparison of trophic function between the globally invasive crayfishes Pacifastacus leniusculus and Procambarus clarkii - Eric R. Larson; Laura A. Twardochleb; Julian D. Olden (Limnology, 2017)

Identifying gene–gene interactions that are highly associated with four quantitative lipid traits across multiple cohorts - Rishika De; Shefali S. Verma; Emily Holzinger; Molly Hall; Amber Burt; David S. Carrell; David R. Crosslin; Gail P. Jarvik; Helena Kuivaniemi; Iftikhar J. Kullo; Leslie A. Lange; Matthew B. Lanktree; et al. (Human Genetics, 2017)

A genome- and phenome-wide association study to identify genetic variants influencing platelet count and volume and their pleiotropic effects - Khader Shameer; Joshua C. Denny; Keyue Ding; Hayan Jouni; David R. Crosslin; Mariza de Andrade; Christopher G. Chute; Peggy Peissig; Jennifer A. Pacheco; Rongling Li; Lisa Bastarache; Abel N. Kho; et al. (Human Genetics, 2014)

Effects of Climate Change, Invasive Species, and Disease on the Distribution of Native European Crayfishes - CÉSAR CAPINHA; ERIC R. LARSON; ELENA TRICARICO; JULIAN D. OLDEN; FRANCESCA GHERARDI (Conservation Biology, 2013)
Climate change will require species to adapt to new conditions or follow preferred climates to higher latitudes or elevations, but many dispersal‐limited freshwater species may be unable to move due to barriers imposed by watershed boundaries. In addition, invasive nonnative species may expand into new regions under future climate conditions and contribute to the decline of native species. We evaluated future distributions for the threatened European crayfish fauna in response to climate change, watershed boundaries, and the spread of invasive crayfishes, which transmit the crayfish plague, a lethal disease for native European crayfishes. We used climate projections from general circulation models and statistical models based on Mahalanobis distance to predict climate‐suitable regions for native and invasive crayfishes in the middle and at the end of the 21st century. We identified these suitable regions as accessible or inaccessible on the basis of major watershed boundaries and present occurrences and evaluated potential future overlap with 3 invasive North American crayfishes. Climate‐suitable areas decreased for native crayfishes by 19% to 72%, and the majority of future suitable areas for most of these species were inaccessible relative to native and current distributions. Overlap with invasive crayfish plague‐transmitting species was predicted to increase. Some native crayfish species (e.g., noble crayfish [Astacus astacus]) had no future refugia that were unsuitable for the modeled nonnative species. Our results emphasize the importance of preventing additional introductions and spread of invasive crayfishes in Europe to minimize interactions between the multiple stressors of climate change and invasive species, while suggesting candidate regions for the debatable management option of assisted colonization. Efectos del Cambio Climático, Especies Invasoras y Enfermedades sobre la Distribución de Cangrejos de Río Europeos Nativos

Using avatar species to model the potential distribution of emerging invaders - Eric R. Larson; Julian D. Olden (Global Ecology and Biogeography, 2012)
Aim Anticipating the potential distributions of emerging invasive species is complicated by the tendency for species distribution models to perform better when both native and invasive range data are available for model development. If invasive range data are lacking, species models are liable to under‐estimate distributions for emerging invaders, particularly for species that are not at equilibrium with their native range environment due to historical factors, dispersal limitation and/or ecological interactions. We demonstrate the potential to use well‐quantified niche shifts from established ‘avatar’ (i.e. the remote or virtual manifestation of an entity) invaders to develop plausible distributions for data‐poor emerging invaders contingent on niche shifts of similar magnitude or character. Location Global. Methods Using the globally invasive crayfishes Pacifastacus leniusculus and Procambarus clarkii as our avatar invaders, we quantify how niche position, size and structure differs between native and total ranges using Mahalanobis distance (a measure of multivariate similarity) and the climate predictors of annual minimum and maximum air temperature. We then generalize patterns of niche shift from these species to the emerging crayfish invader Cherax quadricarinatus . Results Some patterns of niche shifts were similar for Pacifastacus leniusculus and Procambarus clarkii , but niche shifts were of considerably greater magnitude for P. clarkii . When a native range model for C. quadricarinatus was modified with generalized niche shifts similar to Pacifastacus leniusculus and Procambarus clarkii , the potential global distribution for this species increased considerably, including many areas not identified by the native range model. Main conclusions We illustrate the potential to use avatar invaders to provide cautionary, niche shift‐assuming species distribution models for emerging invaders. Many theoretical and applied implications of the avatar species concept require additional investigation, including the development of frameworks to select appropriate avatar species and evaluate the performance of avatar‐derived models for emerging invaders. Despite these research needs, we believe this concept will have considerable utility for predicting vulnerability to invasion by data‐poor species; this is a critical management need because shifting pathways of introduction and climate change will produce many novel, emerging invasive species in the future.

Genetic variants associated with the white blood cell count in 13,923 subjects in the eMERGE Network - David R. Crosslin; Andrew McDavid; Noah Weston; Sarah C. Nelson; Xiuwen Zheng; Eugene Hart; Mariza de Andrade; Iftikhar J. Kullo; Catherine A. McCarty; Kimberly F. Doheny; Elizabeth Pugh; Abel Kho; et al. (Human Genetics, 2012)

Latent Extinction and Invasion Risk of Crayfishes in the Southeastern United States - ERIC R. LARSON; JULIAN D. OLDEN (Conservation Biology, 2010)
Crayfishes are both a highly imperiled invertebrate group as well as one that has produced many invasive species, which have negatively affected freshwater ecosystems throughout the world. We performed a trait analysis for 77 crayfishes from the southeastern United States in an attempt to understand which biological and ecological traits make these species prone to imperilment or invasion, and to predict which species may face extinction or become invasive in the future. We evaluated biological and ecological traits with principal coordinate analysis and classification trees. Invasive and imperiled crayfishes occupied different positions in multivariate trait space, although crayfishes invasive at different scales (extraregional vs. extralimital) were also distinct. Extraregional crayfishes (large, high fecundity, habitat generalists) were most distinct from imperiled crayfishes (small, low fecundity, habitat specialists), thus supporting the “two sides of the same coin” hypothesis. Correct classification rates for assignment of crayfishes as invasive or imperiled were high (70–80%), even when excluding the highly predictive but potentially confounding trait of range size (75–90%). We identified a number of species that, although not currently listed as imperiled or found outside their native range, possess many of the life‐history and ecological traits characteristic of currently invasive or imperiled taxa. Such species exhibit a high latent risk of extinction or invasion and consequently should be the focus of proactive conservation or management strategies. Our results illustrate the utility of trait‐based approaches for taxonomic groups such as invertebrates, for which detailed species‐specific data are rare and conservation resources are chronically limited.

The feasibility of low CO2 concentration targets and the role of bio-energy with carbon capture and storage (BECCS) - Christian Azar; Kristian Lindgren; Michael Obersteiner; Keywan Riahi; Detlef P. van Vuuren; K. Michel G. J. den Elzen; Kenneth Möllersten; Eric D. Larson (Climatic Change, 2010)

Home-field advantage: native signal crayfish (Pacifastacus leniusculus) out consume newly introduced crayfishes for invasive Chinese mystery snail (Bellamya chinensis) - Julian D. Olden; Eric R. Larson; Meryl C. Mims (Aquatic Ecology, 2009)

Does juvenile competition explain displacement of a native crayfish by an introduced crayfish? - Eric R. Larson; Daniel D. Magoulick (Biological Invasions, 2009)

The human FE65 gene: genomic structure and an intronic biallelic polymorphism associated with sporadic dementia of the Alzheimer type - Q. Hu; Walter A. Kukull; Steven L. Bressler; Matthew D. Gray; Judith A. Cam; Eric B. Larson; George M. Martin; Samir S. Deeb (Human Genetics, 1998)